2014
DOI: 10.1111/1750-3841.12328
|View full text |Cite
|
Sign up to set email alerts
|

Application of Different Molecular Techniques for Characterization of Catalase‐Positive Cocci Isolated from Sucuk

Abstract: This study was carried out for the characterization and discrimination of the indigenous Gram positive, catalase-positive cocci (GCC) population in sucuk, a traditional Turkish dry-fermented sausage. Sucuk samples, produced by the traditional method without starter culture were collected from 8 local producers in Kayseri/Turkey and a total of 116 GCC isolates were identified by using different molecular techniques. Two different molecular fingerprinting methods; namely, randomly amplified polymorphic DNA-PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Macrococcus caseolyticus strain YSY1‐12 found in our study has been reported as part of the spoilage microbiota of water‐boiled salted duck stored at 4 °C . However, M. caseolyticus , previously classified in the genus Staphylococcus ( S. caseolyticus ), has also been isolated from fermented fish products, fermented meat products, fermented sausages, raw milk and cheese …”
Section: Discussionmentioning
confidence: 53%
“…Macrococcus caseolyticus strain YSY1‐12 found in our study has been reported as part of the spoilage microbiota of water‐boiled salted duck stored at 4 °C . However, M. caseolyticus , previously classified in the genus Staphylococcus ( S. caseolyticus ), has also been isolated from fermented fish products, fermented meat products, fermented sausages, raw milk and cheese …”
Section: Discussionmentioning
confidence: 53%
“…Similarly, Ozturk et al (2014) reported that a w values of 35 sucuk samples obtained from sucuk producers ranged from 0.710 to 0.930. In another study, Kesmen et al (2014) indicated that a w values of sucuk samples collected from 8 local producers in triplicate in Kayseri were between 0.752 and 0.854. Likewise, Table 2 provides a w values of the salami samples.…”
Section: Resultsmentioning
confidence: 99%
“…Gram staining, catalase, and coagulase test results showed that among the 67 selected colonies, a total of 61 were Gram‐positive, catalase‐positive, and coagulase negative cocci. In previous studies exhibited that Gram‐positive, catalase‐positive, and coagulase negative cocci are associated with traditional fermented sausages produced in Europe (Bonomo, Ricciardi, Zotta, Sico, & Salzano, ; Cachaldora, Fonseca, Franco, & Carballo, ; Kaban & Kaya, ; Kesmen, Yarimcam, Aslan, & Yetim, ; Landeta et al, ; Marty et al, ; Mauriello, Casaburi, Blainotta, & Villani, ; Resch, Nagel, & Hertel, ; Zdolec et al, ), as confirmed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies showed that S. xylosus, S. equorum , and S. saprophyticus have been the most frequently isolated species from traditional fermented sausages. Other species such as S. carnosus , S. caprae , S. epidermidis , S. hominis , S. succinus , S. sciuri , S. vitulinus , and S. warneri are less frequently identified (Bonomo et al, ; Kaban & Kaya, ; Kesmen et al, ; Leroy, Giammarinaro, Chacornac, Lebert, & Talon, ; Mauriello et al, ). We also isolated 10 Macrococcus caseolyticus (formerly Staphylococcus caseolyticus ) strains from sucuk samples.…”
Section: Resultsmentioning
confidence: 99%